A series of new lanthanide benzoates: Syntheses, crystal structures, and luminescent properties. (May 2022) - Meng, Xiaoyu; Liu, Xing; Zhang, Lu; Zhou, Jian; Zou, Hua-Hong; Zhang, Jingjing; Xiang, Dongmei; Zou, Xuan
Abstract: A series of new luminescent lanthanide benzoates [ Ln 2 (phen)2 (bza)4 (Ac)2 ] Ln = Eu (1 ), Gd 3+ (2 ), Tb 3+ (3 ), Dy 3+ (4 ), Tm 3+ (5 ); phen = 1, 10-phenanthroline, Hbza = benzoic acid, Ac − = acetate) and [ Ln 2 (phen)2 (bza)4 (NO3 )2 ] [ Ln = Sm 3+ (6 ), Eu 3+ (7 ), Tb 3+ (8 ), Dy 3+ (9 ), Tm 3+ (10 )] have been hydrothermally prepared by the usage of the π-conjugated phen ligands as chromophores. 1 –5 exhibit binuclear [ Ln 2 (phen)2 (bza)4 (Ac)2 ] moieties built up from two [Ln(phen)] 3+ groups joined together by the bridging bza − and Ac − ligands, while 6 –10 show another binuclear [ Ln 2 (phen)2 (bza)4 (NO3 )2 ] moieties constructed by two [Ln(phen)(NO3 )] 2+ groups linked together by the bridging bza − ligands. These compounds offer the rare examples of binuclear lanthanide benzoates decorated by phen chromophores. Luminescent and sensing properties of 1 –10 were studied, revealing that europium (1 and 7 ) and terbium (3 and 8 ) benzoates can be used as a bifunctional luminescent probe for acetone and Fe 3+ with high efficiency and selectivity. Graphical abstract: This work offers the only example of luminescent lanthanide benzoates incorporating phen chromophores and small auxiliary π-conjugated NO3 − ligands, whose europium benzoate shows good bifunctional sensor targeted for acetone and Fe 3+ ion. Image 1 Highlights: A series of new luminescent lanthanide benzoates were hydrothermally prepared. The Eu 3+ and Tb 3+ complexes shows bifunctional sensor for acetone and Fe 3+ ion. 5 –6 offer the rare examples of lanthanide benzoates incorporating phen chromophores.